Circ_0110251 overexpression alleviates IL-1β-induced chondrocyte apoptosis and extracellular matrix degradation by regulating miR-3189-3p/SPRY1 axis in osteoarthritis - Yawei Zhang; Hengheng Zheng; Baitong Li (Taylor & Francis Group, 2022)
Background Mounting evidence indicates that circular RNAs (circRNAs) are involved in the progression of human diseases, including osteoarthritis (OA). In this study, we focussed on the functions and potential mechanism of circ_0110251 in OA. Methods Quantitative real-time polymerase chain reaction (qRT-PCR) was conducted to determine the expression of circ_0110251, collagen type XI alpha 1 chain (COL11A1), microRNA-3189-3p (miR-3189-3p) and sprouty receptor tyrosine kinase signalling antagonist 1 (SPRY1). The cyclisation analysis of circ_0110251 was analysed by RNase R and Actinomycin D assays. Flow cytometry analysis was conducted to analyse cell apoptosis. Western blot assay was used to measure the levels of extracellular matrix degradation (ECM)-associated markers and SPRY1. Dual-luciferase reporter assay, RNA immunoprecipitation (RIP) assay and RNA pull down assay were performed to analyse the relationships among circ_0110251, miR-3189-3p and SPRY1. Results Circ_0110251 was downregulated in OA cartilage tissues and IL-1β-induced chondrocytes. IL-1β promoted the apoptosis and ECM degradation in chondrocytes, while circ_0110251 overexpression relieved the effects. Circ_0110251 functioned as the sponge for miR-3189-3p and miR-3189-3p overexpression reversed the effect of circ_0110251 on IL-1β-induced chondrocyte damage. Additionally, SPRY1 served as the target gene of miR-3189-3p. MiR-3189-3p inhibition ameliorated IL-1β-induced chondrocyte apoptosis and ECM degradation, while SPRY1 silencing rescued the impacts. Conclusion Circ_0110251 protected chondrocytes from IL-1β-induced apoptosis and ECM degradation in OA via sponging miR-3189-3p and elevating SPRY1.